ACTA ORIENTALIA VILNENSIA EXCHANGE PROGRAMME - Vilnensis, Acta Orientalia (Acta Orientalia Vilnensia, 2011)
The editors of the Acta Orientalia Vilnensia, in co-operation with the Oriental library at Vilnius University, highly welcome a regular exchange of scholarly periodicals publishing on Asian and Middle Eastern studies. For exchange proposals, please contact the secretary of the editorial board. Journals or serial publications received under the programme in 2014: • Acta Asiatica. Bulletin of the Institute of Eastern Studies • Annals of the Bhandarkar Oriental Research Institute • Archív Orientální • Asian Ethnology • Asian Studies Review • Asiatische Studien/Études Asiatiques • Brahmavidya: The Adyar Library Bulletin • Bulletin of the Deccan College Post-Graduate and Research Institute • Cracow Indological Studies • Dao: A Journal of Comparative Philosophy • Folia Orientalia • Indologica Taurinensia • Japanese Journal of Religious Studies • Journal of Sukrtindra Oriental Research Institute • Journal of the Asiatic Society of Mumbai • Journal of the International College for Postgraduate Buddhist Studies • Journal of the Oriental Institute, M.S. University of Baroda • Linguistic and Oriental Studies from Poznan • Monumenta Serica. Journal of Oriental Studies • New Zealand Journal of Asian Studies • Pacific World: Journal of the Institute of Buddhist Studies • Pandanus • Philosophy East and West • Religion East and West • Rocznik Orientalistyczny • Studia Indologiczne • Studia Orientalia • Wiener Zeitschrift für die Kunde Südasiens • ZINBUN